Antimicrobial Activity of Chemokine CXCL10 for Dermal and Oral Microorganisms - Grant O. Holdren; David J. Rosenthal; Jianyi Yang; Amber M. Bates; Carol L. Fischer; Yang Zhang; Nicole K. Brogden; Kim A. Brogden (MDPI AG, 2014)
CXCL10 (IP-10) is a small 10 kDa chemokine with antimicrobial activity. It is induced by IFN-γ, chemoattracts mononuclear cells, and promotes adhesion of T cells. Recently, we detected CXCL10 on the surface of the skin and in the oral cavity. In the current study, we used broth microdilution and radial diffusion assays to show that CXCL10 inhibits the growth of Escherichia coli, Staphylococcus aureus, Corynebacterium jeikeium, Corynebacterium striatum, and Candida albicans HMV4C, but not Corynebacterium bovis, Streptococcus mutans, Streptococcus mitis, Streptococcus sanguinis, Fusobacterium nucleatum, Aggregatibacter actinomycetemcomitans, Poryphromonas gingivalis, or C. albicans ATCC 64124. The reason for the selective antimicrobial activity is not yet known. However, antimicrobial activity of CXCL10 may be related to its composition and structure, as a cationic 98 amino acid residue molecule with 10 lysine residues, 7 arginine residues, a total net charge of +11, and a theoretical pI of 9.93. Modeling studies revealed that CXCL10 contains an α-helix at the N-terminal, three anti-parallel β-strands in the middle, and an α-helix at the C-terminal. Thus, CXCL10, when produced on the surface of the skin or in the oral cavity, likely has antimicrobial activity and may enhance innate antimicrobial and cellular responses to the presence of select commensal or opportunistic microorganisms.